The Social Information Processing Model of Task Design: A Review of the Literature - Thomas, Joe; Griffin, Ricky W. (Academy of Management Review, 1983)
This paper reviews ten studies dealing with the effects of social and information cues in the workplace on employee task perceptions, evaluations, and reactions. The review employs both judgmental and meta-analytic approaches to interpreting the findings. The two basic conclusions of the review are that social and information cues have been shown to consistently influence perceptions and affect, but that the area needs additional theoretical articulation and integration. Unanswered questions and suggestions for future research are identified. (Author)